2011
DOI: 10.5897/ajb11.2694
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of ground water pollution by heavy metals and bioaccumulation of mercury residues in chicken tissues

Abstract: The aim of this study was to investigate the relationship between the concentrations of heavy metals in well water and bioaccumulation of the most abundant metals in chicken tissues in some areas in the province of Mecca Almokaramah, Saudi Arabia. Among the heavy metals (Cd, Zn, Cr, Mn, Cu Hg, Pb and Ni) studied, mercury (Hg) revealed highest in concentration in well waters. The concentration of mercury in ground water, beside in liver, kidney, muscle and blood samples of 10 chickens from each of four poultry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Uap Hg bisa menyebabkan bronkitis, asma dan masalah pernafasan yang tidak permanen. Organ saraf sangat sensitif terhadap segala bentuk Hg dan dapat menyebabkan sejumlah abnormalitas neurologis dan neuropati peripheral pada manusia dan hewan coba (HK Hussein et al 2011). Paparan merkuri dengan dosis yang tinggi dapat menyebabkan kerusakan yang permanen pada otak, ginjal, dan fetus yang sedang tumbuh di dalam uterus.…”
Section: Keracunan Merkuri (Hg)unclassified
See 1 more Smart Citation
“…Uap Hg bisa menyebabkan bronkitis, asma dan masalah pernafasan yang tidak permanen. Organ saraf sangat sensitif terhadap segala bentuk Hg dan dapat menyebabkan sejumlah abnormalitas neurologis dan neuropati peripheral pada manusia dan hewan coba (HK Hussein et al 2011). Paparan merkuri dengan dosis yang tinggi dapat menyebabkan kerusakan yang permanen pada otak, ginjal, dan fetus yang sedang tumbuh di dalam uterus.…”
Section: Keracunan Merkuri (Hg)unclassified
“…Paparan Pb yang berlebihan dapat menyebabkan kerusakan serius pada otak, ginjal, sistem saraf dan selsel darah merah. Individu muda dan fetus lebih rentan terhadap paparan Pb dibandingkan individu dewasa (Hussein et al 2011). Logam Pb dapat diserap melalui beberapa rute seperti pernapasan, kulit, dan mulut.…”
Section: Keracunan Timbal (Pb)unclassified
“…Kidneys accumulate highest levels of mercury compared to brain and liver [33]. Renal toxicity of mercuric chloride is well documented in literature.…”
Section: Renal Systemmentioning
confidence: 99%
“…Inorganic mercury compounds mainly affect renal system. It has been reported that kidneys can accumulate high levels of mercury as compared to brain and liver (Hussein et al, 2011).…”
Section: Impact On Human Health and Environmentmentioning
confidence: 99%